External Powers and North Korea-South Korea Diplomatic Relations: Re-Visiting Historical Context of the Koreas Geo-Political Confrontations - Obikaeze, Chibuike V.; Okwori, Favour O. (Journal of Contemporary International Relations and Diplomacy, 2025)
The diplomatic landscape between North Korea and South Korea since the cessation of the Korean War in 1953 has been continuously influenced by the interplay of external powers, entrenched in a complex web of geopolitical dynamics and confrontations. The establishment of the Demilitarized Zone (DMZ) along the 38th parallel lines marked the beginning of a persistent state of tension and conflict. This is further complicated by the interests of major global powers such as the United States, China, Russia, and Japan. This paper examined the influence exerted by these external actors on the diplomatic security relations between North Korea and South Korea, spanning from the Cold War era to the present time. By integrating the Complex Interdependence Theory as an analytical framework, the research adopted qualitative-descriptive method and content-analysis technique, thereby relying on primary and documentary sources. The findings revealed that the interventions of external actors have played a complex role in shaping the security trajectories of the Korean Peninsula, as well as having significant impact on the diplomatic and trade relations between the Koreas. Consequently, there have been persistent mutual distrust and conflicting national interests which have profoundly exacerbated the ongoing security tensions between the two nations. The study recommended for a renewed and vigorous denuclearization ‘back-door’ diplomacy, at the instance of the United States and Western Great Powers, as well as enhanced bilateral economic cooperation between the two nations